How speech pathology educators conceptualise reflection in practicum contexts influences student learning experiences. Issue 3 (4th May 2021) - Dunne, Michael; Nisbet, Gillian; Penman, Merrolee
ABSTRACT: Reflection is an educational construct used in speech pathology programmes to connect theory with practice within units of study and practicum learning contexts. Speech pathology educators support the integration of this construct to develop lifelong learning skills in speech pathology students. Despite educators' central role in developing student lifelong learning skills, there is no published evidence identifying speech pathology educators' experiences and perceptions of facilitating student reflection. A descriptive qualitative study approach consisting of an initial scoping survey and semi-structured interviews were used to investigate speech pathology educators' experiences and perceptions of facilitating student reflection. Inductive analysis of qualitative data from ten speech pathology educators identified key themes and factors that were salient to educators' experiences and perceptions of facilitating reflection learning in students. Several factors were found to influence whether educators' feedback focuses on the content or the meta-cognitive processes of student reflection. These include educators' conceptualisation of what reflection means, characteristics of student reflection and the practicum context. Speech pathology educators' conceptualisation of what reflection means appears to influence how they perceive and experience reflection as a learning approach with students during practicum. Findings and implications for facilitation of student reflection are discussed.